2021
DOI: 10.1021/acssensors.1c00008
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime-Engineered Ruby Nanoparticles (Tau-Rubies) for Multiplexed Imaging of μ-Opioid Receptors

Abstract: To address the growing demand for simultaneous imaging of multiple biomarkers in highly scattering media such as organotypic cell cultures, we introduce a new type of photoluminescent nanomaterial termed “tau-ruby” composed of ruby nanocrystals (Al2O3:Cr3+) with tunable emission lifetime. The lifetime tuning range from 2.4 to 3.2 ms was achieved by varying the Cr3+ dopant concentration from 0.8% to 0.2%, affording facile implementation of background-free detection. We developed inexpensive scalable production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Excitation of the solid solution nanocrystals as a powder using a 532 nm laser produced a sharp emission line at 695 nm characteristic of substitutional Cr 3+ ions in an Al-rich corundum lattice (Figure 7). 7,37,38 Two shoulders were observed on either side of the sharp emission (Figure 7a). These shoulders, between 670 and 680 nm and between 705 and 715 nm, have been attributed to coupled pairs of Cr 3+ ions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Excitation of the solid solution nanocrystals as a powder using a 532 nm laser produced a sharp emission line at 695 nm characteristic of substitutional Cr 3+ ions in an Al-rich corundum lattice (Figure 7). 7,37,38 Two shoulders were observed on either side of the sharp emission (Figure 7a). These shoulders, between 670 and 680 nm and between 705 and 715 nm, have been attributed to coupled pairs of Cr 3+ ions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…much greater than the Rn thickness (Figure S6). Rn coating with SiO 2 changed the zeta potential to negative ∼ −30 mV 30 and hindered ICG attaching to nanoparticles surface (right panel in Figure 6e). The FRET efficiency, η, is the fraction of the donor excitation energy transferred to the acceptors.…”
Section: Resultsmentioning
confidence: 99%
“…The small size and wide range of optical and magnetic properties make metal oxide nanomaterials particularly attractive candidates for use as analytical probes in chemistry and biology. , For example, a nanoruby (Al 2 O 3 :Cr 3+ ) has a broad absorption spectrum coupled with a single very sharp emission line and quantum efficiency exceeding 80%; these properties make it well suited to applications based on imaging and tracking in complex biological systems. Iron oxide nanoparticles exhibit useful magnetic properties, facilitating fundamental studies of protein adsorption and potential use in biomedical diagnostics and therapy and diagnostics. Recent studies have shown that metal oxides can also be highly effective micronutrient delivery vehicles for nano-enhanced agriculture. Control over the particle surface could increase their efficiency and effectiveness, targeting specific parts of plants or bodies for delivery of nutrients or drugs.…”
Section: Introductionmentioning
confidence: 99%